A new approach to risk attribution and its application in credit risk analysis - Christoph Frei (Risks, 2020)
How can risk of a company be allocated to its divisions and attributed to risk factors? The Euler principle allows for an economically justified allocation of risk to different divisions. We introduce a method that generalizes the Euler principle to attribute risk to its driving factors when these factors affect losses in a nonlinear way. The method splits loss contributions over time and is straightforward to implement. We show in an example how this risk decomposition can be applied in the context of credit risk.
Keywords: 330; risk attribution; risk allocation; credit risk; Euler principle; risk factors